2019
DOI: 10.1530/joe-18-0573
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of testosterone in pancreatic β cell function and insulin secretion

Abstract: One of the most sexually dimorphic aspects of metabolic regulation is the bidirectional modulation of glucose homeostasis by testosterone in male and females. Severe testosterone deficiency predisposes men to type 2 diabetes (T2D), while in contrast, androgen excess predisposes women to hyperglycemia. The role of androgen deficiency and excess in promoting visceral obesity and insulin resistance in men and women respectively is well established. However, although it is established that hyperglycemia requires β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 71 publications
2
58
2
Order By: Relevance
“…Testosterone deficiency leads to decreased LBM, increased abdominal fat mass, and ultimately increased insulin resistance in males [ 27 ]. Additionally, β-cells have androgen receptors, and testosterone potentiates glucose-stimulated insulin secretion, and it has similar insulinotropic action as glucagon-like peptide-1 [ 27 ]. Testosterone deficiency impairs glucose metabolism to increase type 2 diabetes risk in elderly men.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone deficiency leads to decreased LBM, increased abdominal fat mass, and ultimately increased insulin resistance in males [ 27 ]. Additionally, β-cells have androgen receptors, and testosterone potentiates glucose-stimulated insulin secretion, and it has similar insulinotropic action as glucagon-like peptide-1 [ 27 ]. Testosterone deficiency impairs glucose metabolism to increase type 2 diabetes risk in elderly men.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that an increased risk of EC is associated with increased exposure to androgen, including variation in AR genes 30 , 31 and PCOS, leading to hyperandrogenism. Hyperandrogenism is correlated to a high tolerance to insulin 32 - 34 , which can lead to insulin level increases and other metabolic syndromes. Excessive androgen has been reported to alter autophosphorylation of the insulin receptor in the ovary of a woman with PCOS, resulting in a much higher tolerance to insulin 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that androgens could increase the expression of IGF-I in satellite cells and promote myogenesis in humans [39]. The high concentration of androgen could promote the secretion of insulin by potentiating the insulinotropic action of glucagonlike peptide-1 (GLP-1) in the study of rats [40] but had no significant effect on the secretion of thyroxine and triiodothyronine [41]. Although all of the cattle were in the stage of sexual maturity throughout the 6-month experiment, the androgen concentration might differ between the two breeds and may have affected the secretion of growth-related hormones in this study, but this also needs to be confirmed by further experiments.…”
Section: Discussionmentioning
confidence: 99%